Esophageal carcinoma: Ex vivo evaluation by high‐spatial‐resolution T2‐mapping MRI compared with histopathological findings at 3.0T. Issue 6 (6th October 2016) - Wei, Yi; Wu, Sen; Gao, Feifei; Sun, Tingyi; Zheng, Dandan; Ning, Peigang; Zhao, Cuihua; Li, Ziyuan; Li, Xiaodong; Li, Linlin; Zhu, Shaocheng
Abstract : Purpose: To prospectively determine the feasibility of T 2 ‐mapping magnetic resonance imaging (MRI) to quantitatively describe the signal characteristics of the normal esophageal wall and assess the depth of esophageal wall invasion by carcinoma at 3.0T. Materials and Methods: Thirty‐two patient specimens, each having foci of carcinoma, were studied using 3.0T MR. Freehand regions of interest were placed to measure the T 2 value of the normal esophageal layers and were compared with the regions of carcinoma. Three independent readers reviewed the MR images to evaluate the depth of carcinoma invasion; when the three radiologists could not fully agree with each other, the final stage was determined by consensus. The Games‐Howell test was used to compare the difference between the normal esophageal layers and carcinoma. Spearman correlation coefficient analysis was used to compare the stage at MRI with that at histopathological analysis. The interobserver agreement was compared with Cohen's kappa. The sensitivity, specificity, and accuracy for detecting carcinoma invasion were calculated. Results: The T 2 values between the carcinoma and normal esophageal layers were different (all P < 0.01), except for the inner circular muscle ( P = 0.511). The T 2 value of each layer of the normal esophageal wall was also different from that of the adjacent layer (all P < 0.01). In 29 of 32 lesions, the depth of the esophageal wall invasion determined by MR was consistent with the histopathological stage ( r = 0.969, P < 0.001). The sensitivity, specificity, and accuracy were 80%, 96.3%, and 93.8%, respectively, for invasion into the mucosa; 77.8%, 95.7%, and 90.6%, respectively, for invasion into submucosa; 100%, 95.8%, and 96.9%, respectively, for invasion into muscularis propria; and 100%, 100%, and 100%, respectively, for invasion into the adventitia. Conclusion: T 2 ‐mapping MR images obtained using a 3.0T MR scanner can be used to depict the precise histopathological layers of the esophageal wall clearly and provide excellent diagnostic accuracy for assessing esophageal carcinoma invasion. Level of Evidence : 1 Technical Efficacy : Stage 2 J. MAGN. RESON. IMAGING 2017;45:1609–1616